2020
DOI: 10.1002/adfm.201910744
|View full text |Cite
|
Sign up to set email alerts
|

Multiplexed Nondiffracting Nonlinear Metasurfaces

Abstract: Metasurfaces and planar photonic nanostructures have drawn great interest from the optical scientific community due to their diverse abilities of manipulating electromagnetic waves and high integration. Most metasurfaces launch diffracting waves, and thus suffer from divergence, short working distance, and instability. Although much effort has been devoted to researching nondiffracting metasurfaces which can launch electromagnetic waves with constant transverse intensity profiles in free‐space propagation, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 55 publications
0
24
0
Order By: Relevance
“…By exploiting the concept of the PB phase in the nonlinear optical regime, many interesting functional devices such as nonlinear lenses [102][103][104] , nonlinear encryption [105] , and nonlinear imaging [106,107] , have been proposed. The multidimensional nonlinear polarization response of nano-material was achieved in a single heterodyne measurement by active manipulation of the polarization states of incident light [108] , and a new kind of metasurface-based THz emitter with the polarization and phase of THz waves finely controlled was demonstrated [109] .…”
Section: Pb Phase In the Nonlinear Regimementioning
confidence: 99%
“…By exploiting the concept of the PB phase in the nonlinear optical regime, many interesting functional devices such as nonlinear lenses [102][103][104] , nonlinear encryption [105] , and nonlinear imaging [106,107] , have been proposed. The multidimensional nonlinear polarization response of nano-material was achieved in a single heterodyne measurement by active manipulation of the polarization states of incident light [108] , and a new kind of metasurface-based THz emitter with the polarization and phase of THz waves finely controlled was demonstrated [109] .…”
Section: Pb Phase In the Nonlinear Regimementioning
confidence: 99%
“…The nonlinear geometric phase (NGP) metasurfaces have been employed for various applications in the nonlinear optical regime, such as multiplexed nonlinear holography, 75−78 optical information encoding and encryption, 79,80 control of nonlinear optical spin and orbital angular momentum and nonlinear vortex beam generation, 81−83 generation of nondiffraction harmonic signals, 84 nonlinear metalens and imaging systems, 85,86 integrated THz generation and manipulation, 87,88 full complex amplitude control of harmonic signals, 89 quasicrystal nonlinear metasurfaces, 90 nonlinear optical diffraction, 91 asymmetric optical transport, 92 and others. 93−95 It was shown that the different geometric phases that are involved in the linear and nonlinear optical interactions provide new degrees of freedom for generating wavelength and spin multiplexed information channels.…”
Section: ■ Nonlinear Metasurfacesmentioning
confidence: 99%
“…The nonlinear geometric phase (NGP) metasurfaces have been employed for various applications in the nonlinear optical regime, such as multiplexed nonlinear holography, optical information encoding and encryption, , control of nonlinear optical spin and orbital angular momentum and nonlinear vortex beam generation, generation of nondiffraction harmonic signals, nonlinear metalens and imaging systems, , integrated THz generation and manipulation, , full complex amplitude control of harmonic signals, quasi-crystal nonlinear metasurfaces, nonlinear optical diffraction, asymmetric optical transport, and others. It was shown that the different geometric phases that are involved in the linear and nonlinear optical interactions provide new degrees of freedom for generating wavelength and spin multiplexed information channels . The nonlinear metasurfaces can also be designed to control the local amplitude by arranging multiple nanostructures of identical shapes but different orientations into each unit cell. , It should be noted that besides NGP metasurfaces, there are also other ways to achieve control of the nonlinearity phase in harmonic generations, such as by tailoring the geometry of each individual nanostructure of the metasurface. …”
Section: Nonlinear Metasurfacesmentioning
confidence: 99%
“…The latest advances in metasurfaces revealed their great advantages for nonlinear wave generation and manipulation. [ 31–50 ] The phase‐matching condition in nonlinear process can be significantly relaxed in metasurfaces since their thickness is at the subwavelength scale. Meanwhile, the localized surface plasmonic resonances in metasurfaces can generate strong enhancement of the electromagnetic fields near the nanoparticles and can greatly boost the efficiency of high harmonic generation.…”
Section: Introductionmentioning
confidence: 99%
“…[44,45] Nonlinear phase-modulated metasurfaces have been used to realize complete control over the propagation of the high harmonic generation. [46][47][48][49][50] However, previous nonlinear phase-modulated metasurfaces suffer from intrinsic noises due to the loss of intensity information, and such phase-only metasurfaces also cannot realize intensity-only applications such as resolution test targets. Simultaneous manipulation of amplitude and phase of the nonlinear optical signals based on metasurface, which is eagerly anticipated by the scientific community, has not been well explored yet.…”
Section: Introductionmentioning
confidence: 99%